Use the allusion in poetry Hoshang Ebtehaj (Saye) - نصیف جاسم محمد; شکري رشید جیهاد (Al-Adab Journal, 2018)
If we take into consideration the results that have been reached in this research, Can say that the contemporary Iranian poet Hoshang Ebtehaj used allusion good use in his poetry, it has benefited from this literary industry (a moral industries magnificent art) in the poetic effects at large. Therefore, the analysis and interpretation of many of the poems Hoshang Ebtehaj requires knowledge and understanding of his allusions. Interested in this research is by taking advantage of the style of content analysis to extract kinds of allusions in the poetry of Hoshang Ebtehaj (Saye) In two a collection of poems Tasyan and Siah mashq. On the basis of the diversity of content on the researcher to study it in five axes to make it accessible to the reader.The first of which dealt with the allusion to the stories of the prophets as his reversal was widely used in poetry dedicate significant poet of his poems in reference to the part where the incidents of life of the Prophets Photos details of their lives and important events of their lives in his poetry. The diversity of sources of allusions in this axis was the result of informed capacity in the area of ​​the prophets stories.The second axis included the allusion to the Iranian stories alia, to suggest stories and mythical figures and historical, such as the story of Siavash, Rustam, Sohrab, Zal and Phoenix. The third axis was devoted researcher for the allusion to the lyrical and romantic stories that have had a significant impact in his poetry alia, the story of Khosrow Parviz and Farhad and Laila and Majnoon. The poet, through the use of this kind of hint reversal of creativity in the picture and linguistic content invented his sense of delicate and wide imagination attractive images.In the fourth axis cared researcher alluded to the names of the poets Such as Hafez, Sanai and Bahar and ... researcher noted here that the poet as well as he hinted at some of the poets were within the lines of poetry about in his poetry. The latter type of tip used by the poet is a reference to the allusions Universality , including the story of Patrice Lumumba said the poet through allusion to the story of Lumumba pointed to the unjust and tyrannical governments in human societies. The use of each of these types of allusion in poetry Hoshang in her jubilation was an influential and effective role in enriching the imagination and manifestations noodles.